Use of thiopurines is not a risk factor for post-ERC pancreatitis in patients with primary sclerosing cholangitis. Issue 8 (August 2021) - Koskensalo, Vilja; Aronen, Pasi; Färkkilä, Martti; Kylänpää, Leena; Lindström, Outi; Rainio, Mia; Udd, Marianne; Jokelainen, Kalle; Tenca, Andrea
Abstract: Introduction: Risk of post-ERC pancreatitis (PEP) in patients with primary sclerosing cholangitis (PSC) is 1–7.8%. PSC is often associated with inflammatory bowel disease and autoimmune hepatitis, which are usually treated with thiopurines. The role of thiopurines in PEP risk is still unclear. Aims and methods: We evaluated the thiopurine use in PEP. The data of 354 PSC patients who underwent 985 ERCs between 2009 and 2018 were collected. 177 patients treated with thiopurines (study group, SG) and 177 controls (CG) were matched with a propensity score (PSM). Odds ratios (ORs) with 95% confidence interval (95% CI) were calculated. Multivariable logistic regression analysis and generalized linear mixed model were performed. The P-value <0.05 was significant. Results: In matched data, 472 ERCs were performed in SG and 513 in CG. Thiopurines were used in 373/472 (79.0%) ERCs in SG. The PEP rate was 5.3% in SG and 5.7% in CG ( p  = 0.889). Unintentional pancreatic duct cannulation (OR 1.28, 95%CI 1.07–1.51, p  = 0.004), and periampullary diverticulum (OR 4.87, 95%CI 1.72–11.98, p  = 0.001) increased the risk of PEP. Conclusion: Prior or present thiopurine use did not increase the risk of PEP.